The Angle Adjustment System of The Solar Energy to Electrical Energy Converter Practice Tool - Stieven Netanel Rumokoy; I Gede Para Atmaja; Adriyan Warokka; Yosua O. Sihombing; Christian O. Pelealu (CCIT Journal, 2023)
Practical tools need to be created to represent the conditions of a system to support the learning process. In the learning process, especially when studying the utilization of solar energy, a practical tool is required to describe the system of solar panel installation. The practical tool for converting solar energy to electrical energy needs to depict the installation system that occurs during the installation of solar panels. This study aims to develop an angle adjustment system in the practical tool for converting solar energy to electrical energy that can represent the changes in angles and the amount of energy that can be obtained. The methodology begins with a literature study and is followed by the design and testing of the tool. The results obtained show that the Angle Adjustment System in the practical tool for converting solar energy to electrical energy has been able to represent the conditions of solar panel installation. The more perpendicular the light source is to the surface of the solar panel, the greater the amount of electrical energy that can be obtained.